Os efeitos de um programa de atividade física de carga progressiva nas propriedades físicas e na força óssea de ratas osteopênicas - Renno, Ana Claudia Muniz; Faganello, Flavia Roberta; De Moura, Fernanda Mendes; Dos Santos, Nádia Slemer Andrade; Tirico, Renata Passarelli; Bossini, Paulo Sérgio; Zuanon, Jose Antonio [UNESP]; Benatti Neto, Carlos[UNESP]; Parizotto, Nivaldo Antonio [UNESP] (FapUNIFESP (SciELO), 2007)
Background: Many studies have shown that physical exercises are able to stimulate bone formation and increase bone mass, constituting a therapeutic modality to treat bone loss due to osteoporosis. However, some points about the intensity, duration and frequency of the exercises remain confusing and contradictory. Thus, the aim of this study was to determine the effects of a progressive loading exercise program on femur of osteopenic rats. To induce osteopenia we used the animal model of ovariectomy (OVX). Forty animals was studied and divided into 4 groups: sham-operated sedentary (SS); ovariectomy-sedentary (OS); sham-operated training (ST) and ovariectomy training (OT). The trained groups performed jumps into water: 4 series of 10 jumps each, with an overload of 50% to 80% of the animal's body weight, during 8 weeks. Femora were submitted to a physical properties evaluation, a biomechanical test, calcium and phosphorus content measurement and a morphometric histological evaluation. Results: osteopenic animals showed a decrease of bone strength and lower values of bone weights, bone density and calcium content. The exercised osteopenic rats showed higher values of geometrical, physical properties, bone strength and calcium content compared to controls. The results of the present study indicate that the progressive loading exercise program had stimulatory effects on femora of osteopenic rats. It seems that the intensity and duration of the protocol used produced bone structural adaptations, which contributed to reverse bone loss due to ovariectomy.
The effects of a progressive loading exercise program on femoral physical properties and strength of osteopenic rats
Keywords: Osteoporosis; Ovariectomy; Physical exercise; Rats